Lessons Learned From the United States Ocean Observatories Initiative - Smith, Leslie M.; Yarincik, Kristen; Vaccari, Liana; Kaplan, Maxwell B.; Barth, John A.; Cram, Geoffrey S.; Fram, Jonathan P.; Harrington, Michael; Kawka, Orest E.; Kelley, Deborah S.; Matthias, Paul; Newhall, Kristopher; et al. (Frontiers in Marine Science, 2019)
The Ocean Observatories Initiative (OOI) is a United States National Science Foundation-funded major research facility that provides continuous observations of the ocean and seafloor from coastal and open ocean locations in the Atlantic and Pacific. Multiple cycles of OOI infrastructure deployment, recovery, and refurbishment have occurred since operations began in 2014. This heterogeneous ocean observing infrastructure with multidisciplinary sampling in important but challenging locations has provided new scientific and engineering insights into the operation of a sustained ocean observing system. This paper summarizes the challenges, successes, and failures experienced to date and shares recommendations on best practices that will be of benefit to the global ocean observing community.